Indicadores de vulnerabilidad al cambio climático: un estudio en comunidades pesqueras de Tacna, región al sur del Perú - Moreno-Salazar-Calderón, Khiara Aliyah Bet (2023)
The study of indicators of exposure, sensitivity, and adaptive capacity regarding vulnerability to climate change aims to achieve a better understanding of the key indicators affecting communities and to facilitate responsible authorities in implementing mitigation actions. The objective of the study was to identify the main indicators of vulnerability to climate change in fishing communities in the Tacna region. A sample of 255 artisanal fishermen, duly registered in fishing associations along the coast of Tacna, organized in eight fishing communities: Santa Rosa, Los Palos, Yarada Baja, Llostay, Boca del Río, Vila Vila, Morro Sama, and Ite, was considered. Primary source information was used through the application of a questionnaire consisting of 32 indicators. The findings of this research indicate that the main indicator is the dependence on fishing, so increasing non-dependence on fishing reduces the level of vulnerability to climate change in these communities; additionally, it is found that exposure and sensitivity variables do not influence vulnerability, and greater adaptive capacity reduces vulnerability.